Proceedings of the 16th ACM Workshop on Hot Topics in Networks 2017
DOI: 10.1145/3152434.3152895
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges of Ad-based Measurements from the Edge of the Network

Abstract: For many years, the research community, practitioners, and regulators have used myriad methods and tools to understand the complex structure and behavior of ISPs from the edge of the network. Unfortunately, the nature of these techniques forces the researcher to find a balance between ISP-coverage, user scale, and accuracy. In this paper we present AdTag, a network measurement paradigm that leverages the opportunistic nature of online targeted advertising to measure the Internet from the edge of the network. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…As we can see in Table 1, all previous DNS studies used methods that fall short at meeting simultaneously the geographical and temporal scope, reproducibility, and openness requirements. To overcome the limitations of the state-ofthe-art, we adapt AdTag [10], a flexible JavaScript-based methodology to measure the global infrastructure of recursive DNS resolvers and users' DNS choices at a global scale and in a short timescale. Our web-based measurement method leverages a purpose-built lightweight JavaScript code which probes the configured recursive DNS resolver from the browser.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we can see in Table 1, all previous DNS studies used methods that fall short at meeting simultaneously the geographical and temporal scope, reproducibility, and openness requirements. To overcome the limitations of the state-ofthe-art, we adapt AdTag [10], a flexible JavaScript-based methodology to measure the global infrastructure of recursive DNS resolvers and users' DNS choices at a global scale and in a short timescale. Our web-based measurement method leverages a purpose-built lightweight JavaScript code which probes the configured recursive DNS resolver from the browser.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…2) Our IP geolocation effort is subject to the Maxmind's geo-mapping accuracy, which previous studies have reported as good enough at the country granularity for the majority of the cases [22]. We have also considered RIPE IPmap, 10 but the response time and coverage of this service do not meet our requirements. 3) Our NS records the public IP address of the recursive resolver and end user connecting, but it only supports IPv4.…”
Section: Methods Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will serve to fix identified biases in the data sample, but also to conduct specific analysis of the browser market landscape such as analyze the market share for a particular demographic group (based on age and/or sex), analyze the presence of insecure browser versions and identify its associated IPs, etc; (iii) it should guarantee that each browser instance represents a single data sample in the collected dataset. To achieve these goals, we propose the utilization of AdTag [10], and active measurements platform, contrary to the passive measurements used so far. In particular, our approach relies on the online advertising ecosystem.…”
Section: Active Measurement Based Methodology For Monitoring Thementioning
confidence: 99%
“…In this paper, we propose the use of AdTag [10], an active measurement platform leveraging display ads as measurement vantage points, to monitor the browser market landscape. This approach overcomes the described limitations of traditional passive methodologies and offers the three main functional requirements mentioned above: scalability, accessibility and targeting capabilities.…”
Section: ) Geographical and Demographic Targeting Capabilitymentioning
confidence: 99%